Maternal Serum Interleukin6 Level in Correlation with Preterm Delivery - Noviyanti Noviyanti; Hermie M M Tendean; Juneke J Kaeng (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine the correlation between maternal serum Interleukin-6 (IL-6) serum level with preterm delivery. Methods: We performed an observational cross-sectional study of 30 pregnant women between 21 to 36 week gestational age with and wthout labour (delivery) in Prof. Dr. RD. Kandou Hospital Manado. Samples were collected with consecutive sampling method. Data was analyzed using Mann-Whitney test with significance level of p